(untitled) (Global Journal of Science Frontier Research, 2026)
Abstract- This paper postulates: The existence of The Zeroth of Generation Zh of Fermion. Zh comprises four Zero-Mass particles (Ψ(0) = (α(0), β(0), γ(0), δ(0))). Particle Ψ(0) could offer the guidance to accomplish a unified mass theory of twelve elementary fermions in particle physics.